Investigation of Bubble Characteristics by Photographic Method - S. Amirzadeh; J.S Moghaddas (Iranian Journal of Chemical Engineering)
Most industrial operating units are basically in contact with two gas and liquid phases. Bubble characteristics over the last years have been determined through different methods. In this project a mass transfer system has been designed for absorbing gas bubbles by liquid phase. The mass transfer and hydrodynamic behavior in the wake of single rising air bubbles were investigated by using an image analysis method and empirical relations. By considering these methods, the overall bubble properties including the size of single bubble, shape, path, rising velocity and mass transfer coefficient were studied and measured. The investigation was developed with 0.15×0.15×0.35 m3 bubble column and nozzle diameter (0.5, 1, 1.5, 2, 2.5 mm) in different liquids considering viscose changes. Moreover, from the results obtained, it can be concluded that the increase of nozzle diameter increases the bubble diameter which results in reduction of velocity and mass transfer coefficient. This is a fact that, by raising the viscosity of liquid phase the bubble diameter stands at the highest level and on the contrary velocity and mass transfer coefficient stand at the lowest level. So according to these outcomes we can conclude that, the diameter of bubble depends on physical properties of fluids and has a direct relation with nozzle diameter.